Geochemical Implications of Gas Leakage associated with Geologic CO2 StorageA Qualitative Review - Harvey, Omar R; Qafoku, Nikolla P; Cantrell, Kirk J; Lee, Giehyeon; Amonette, James E; Brown, Christopher F (Environmental science & technology, 2013)
Gas leakage from deep storage reservoirs is a major risk factor associated with geologic carbon sequestration (GCS). A systematic understanding of how such leakage would impact the geochemistry of potable aquifers and the vadose zone is crucial to the maintenance of environmental quality and the widespread acceptance of GCS. This paper reviews the current literature and discusses current knowledge gaps on how elevated CO2 levels could influence geochemical processes (e.g., adsorption/desorption and dissolution/precipitation) in potable aquifers and the vadose zone. The review revealed that despite an increase in research and evidence for both beneficial and deleterious consequences of CO2 migration into potable aquifers and the vadose zone, significant knowledge gaps still exist. Primary among these knowledge gaps is the role/influence of pertinent geochemical factors such as redox condition, CO2 influx rate, gas stream composition, microbial activity, and mineralogy in CO2-induced reactions. Although these factors by no means represent an exhaustive list of knowledge gaps we believe that addressing them is pivotal in advancing current scientific knowledge on how leakage from GCS may impact the environment, improving predictions of CO2-induced geochemical changes in the subsurface, and facilitating science-based decision- and policy-making on risk associated with geologic carbon sequestration.